From the Desk of Editor in Chief Vol.28(2) 2010 - Islam, Quazi Tarikul (Journal of Bangladesh College of Physicians and Surgeons, 2010)
DOI: 10.3329/jbcps.v28i2.5380 J Bangladesh Coll Phys Surg 2010; 28: 140